Arah Pengembangan Diri Siswa SMP dari Perspektif Multiple Intelligence - Putri Ria Angelina; Naila Haerani (Prophetic guidance and counseling journal, 2021)
The challenges of the times require the adaptability of students. The development of the potential of multiple intelligences is expected to be a real support. The purpose of this study was to determine the profile of multiple intelligences possessed by students. The method used is a quantitative method with a survey method. The result of this study is that the highest multiple intelligence profile is in interpersonal, musical and kinesthetic intelligenceAbstrakTantangan zaman memerlukan daya adaptasi handal dari peserta didik. Pengembangan potensi dari kecerdasan jamak diharapkan mampu menjadi penunjang yang nyata. Tujuan dari penelitian ini adalah untuk mengetahui profil multiple intelligenceyang dimiliki peserta didik. Metode yang digunakan adalah kuantitatif dengan metode survey. Hasil penelitian ini adalah profil multiple intelligenceyang tertinggi ada pada kecerdasan interpersonal, musik dan kinestetik.